Analisis Kinerja Efisiensi Bank Komersial Go Public Serta Hubungannya Dengan Regulasi Corporate Governance dan Indikator Kebijakan Moneter Di Indonesia - Rama Deka Putra; Didit Supriyadi; Sonny Hersona (Entrepreneurship Faculty, Universitas Garut, 2022)
This research aims at predicting the effectiveness of corporate governance regulation in Indonesia (PBI No. 8/4/PBI 2006 and PBI No. 8/14/PBI 2006) through indicator of efficiency of go public commercial bank, and also analyzing the relation between indicator of monetary policy toward efficiency of go public commercial bank in Indonesia. This research used non-parametric frontier approach, that is Data Envelopment Analysis (DEA), wilcoxon signed ranks deviation test, and parametric approach two stage least square. The research sample was drawn through observation of Indonesian commercial banks which have been go public consistently since 2003-2008. Following Abidin (2007) input and output variables in efficiency performance were measured by intermediation of maximize output approach, while indicator of monetary policy was projected by the placement of go public commercial banks at GWM and SBI and explanatory addition that is banks’ Asset and NIM. The results show that there is an average difference of efficiency before and after the implementation of Indonesian banks regulation (regulation effectiveness), insignificant influence of bank placement at GWM and SBI toward the efficiency (indicator monetary policy did not influence banks’ efficiency yet). Penelitian ini bertujuan untuk memprediksi efektivitas regulasi corporate governance di Indonesia (PBI No. 8/4/PBI 2006 dan PBI No. 8/14/PBI 2006) melalui indikator efisiensi bank umum go public, serta menganalisis hubungan antara indikator kebijakan moneter terhadap efisiensi bank umum go public di Indonesia. Penelitian ini menggunakan pendekatan non-parametrik frontier yaitu Data Envelopment Analysis (DEA), uji deviasi peringkat bertanda wilcoxon, dan pendekatan parametrik two stage least square. Sampel penelitian diambil melalui observasi terhadap bank umum Indonesia yang telah go public secara konsisten sejak tahun 2003-2008. Mengikuti Abidin (2007) variabel input dan output dalam kinerja efisiensi diukur dengan pendekatan intermediasi memaksimalkan output, sedangkan indikator kebijakan moneter diproyeksikan dengan penempatan bank umum go public pada GWM dan SBI dan tambahan penjelas yaitu Aset dan NIM bank. . Hasil penelitian menunjukkan bahwa terdapat perbedaan rata-rata efisiensi sebelum dan sesudah penerapan regulasi perbankan Indonesia (efektifitas regulasi), pengaruh penempatan bank pada GWM dan SBI tidak signifikan terhadap efisiensi (indikator kebijakan moneter belum mempengaruhi efisiensi bank).